Analysis of the Law of Insanity Defense in the United Arab Emirates - Ajmal, Ali; Rasool, Faiza (Annals of Human and Social Sciences, 2024)
The objective of this research is to analyze the law on insanity defense in the United Arab Emirates. The criminal law of the United Arab Emirates recognizes the principle of the defense of insanity against the criminal liability of an accused. The doctrinal legal analysis approach was adopted to study the defense of insanity in the United Arab Emirates. The defense of insanity in the United Arab Emirates is dealt with under Article 138 of Federal Law No. 31 (2021), which primarily revolves around the principle of the complete inability to control one’s actions at the time of perpetration of an offense due to mental disorders. However, the role of medical opinion is pivotal in determining the plea of insanity. This law can be further developed by amending it and inculcating insights from the latest developments in mental health sciences.